Vous êtes sur la page 1sur 8

# Mathematical induction

Mathematical induction is a method of mathematical proof typically used to establish that a given statement is true of all natural numbers (positive integers). It is done by proving that the first statement in the infinite sequence of statements is true, and then proving that if any one statement in the infinite sequence of statements is true, then so is the next one. The method can be extended to prove statements about more general well-founded structures, such as trees; this generalization, known as structural induction.

E x a m p l es
P r o b l e m 1: Use m a t h e ma t i ca l i n d uc t i o n to p ro ve t h a t 1 + 2 + 3 + ... + n = n ( n + 1 ) / 2 fo r a l l posi t i v e i n t ege rs n. Sol u t i o n t o P r o b l e m 1:

## STEP 1: We f i r s t show t h a t p (1) is t r u e . Le f t Side = 1 R ig h t Si de = 1 (1 + 1) / 2 = 1

Bo t h sides of t h e sta te me n t a re equa l hence p (1) is t r u e . STEP 2: We now assume t h a t p (k) i s t r u e 1 + 2 + 3 + ... + k = k ( k + 1) / 2
1

## Jasvinder Singh, jasvinder.singh13@rediffmail.com

and show t h a t p ( k + 1) is t r u e by add i n g k + 1 to bot h si des of t h e above sta te me n t 1 + 2 + 3 + ... + k + (k + 1) = k ( k + 1) / 2 + (k + 1) = ( k + 1)( k / 2 + 1) = ( k + 1)( k + 2) / 2

## W h ic h is t h e sta te men t p( k + 1).

P r o b l e m 2: P rove t h a t 1
2

+ 2

+ 3

+ ... + n

= n ( n + 1 ) (2 n + 1)/ 6

## S ta te me n t P (n) is def i ned by 1

2

+ 2

+ 3

+ ... + n

= n (n + 1) (2n + 1)/ 2

## STEP 1: We f i r s t show t h a t p (1) is t r u e . Le f t Side = 1

2

= 1

R ig h t Si de = 1 (1 + 1) (2 * 1 + 1)/ 6 = 1

## STEP 2: We now assume t h a t p (k) i s t r u e 1

2

+ 2

+ 3

+ ... + k

= k ( k + 1) (2 k + 1)/ 6

## and show t h a t p ( k + 1) is t r u e by add i n g ( k + 1) t h e above sta te me n t 1

2

to bo t h sides of

+ 2

+ 3

+ ... + k

+ (k + 1)

= k ( k + 1) (2 k + 1)/ 6 + (k + 1)

## Set common denom i n a t o r an d fac to r k + 1 on t h e r i g h t side = ( k + 1) [ k (2 k + 1)+ 6 (k + 1) ] /6

E x p a n d k (2 k + 1)+ 6 ( k + 1) = ( k + 1) [ 2 k
2

+ 7 k + 6 ] /6
2

No w fac to r 2 k

+ 7 k + 6.

= ( k + 1) [ ( k + 2) (2 k + 3) ] /6

## We h ave sta r t e d f ro m t h e sta te me n t P(k) an d ha ve show n t h a t 1

2

+ 2

+ 3

+ ... + k

+ (k + 1)

= (k + 1) [ (k + 2) (2 k + 3) ] /6

## W h ic h is t h e sta te men t P(k + 1).

P r o b l e m 3: Use m a t h e ma t i ca l i n d uc t i o n to p ro ve t h a t 1
3

+ 2

+ 3

+ ... + n

= n

( n + 1)

/ 4

3

+ 2

+ 3

+ ... + n

= n

(n + 1)

/ 4

## STEP 1: We f i r s t show t h a t p (1) is t r u e . Le f t Side = 1

3

= 1
2

R ig h t Si de = 1

(1 + 1)

/ 4 = 1

## hence p (1) is t r u e . STEP 2: We now assume t h a t p (k) i s t r u e 1

3

+ 2

+ 3

+ ... + k

= k

(k + 1)

/ 4

3

to bo t h sides + ... + k
2 3

+ 2

+ 3

+ (k + 1)

= k

(k + 1)

/ 4 + ( k + 1)

fac to r (k + 1) = ( k + 1)
2

on t he r i g h t side / 4 + (k + 1) ]

[ k

2

[ k

+ 4 k + 4 ] / 4
2

[ ( k + 2)

] / 4

3

+ 2

+ 3

+ ... + k

+ (k + 1)

= (k + 1)

[ (k + 2)

] / 4

## P r o b l e m 4: P rove t h a t fo r an y posi t i v e i n t e ge r n u m be r n , n Sol u t i o n t o P r o b l e m 4:

+ 2 n is d i v i s i b l e by 3

## S ta te me n t P (n) is def i ned by n

3

+ 2 n is d i v i s i b l e by 3

## STEP 1: We f i r s t show t h a t p (1) is t r u e . L e t n = 1 an d calcu l a t e n 3 + 2n 1

3

+ 2(1) = 3

3 is d i v i s i b l e by 3

## hence p (1) is t r u e . STEP 2: We now assume t h a t p (k) i s t r u e k

3

+ 2 k i s d i v i s i b l e by 3

is equ i va le n t to k

+ 2 k = 3 M , w he re M is a posi t i ve i n t e ge r.
3

## We now conside r t h e a lgeb ra ic exp ression (k + 1) expan d i t and g rou p l i k e te r ms ( k + 1) = [ k

3 3

+ 2 ( k + 1);

+ 2 ( k + 1) = k
2

+ 3 k

+ 5 k + 3

+ 2 k ] + [3 k
2

+ 3 k + 3]
2

= 3 M + 3 [ k

+ k + 1 ] = 3 [ M + k

+ k + 1 ]

## Jasvinder Singh, jasvinder.singh13@rediffmail.com

P r o b l e m 5: P rove t h a t 3
n

> n
n

fo r n = 1, n = 2 and use t he ma t h e m a t i ca l i n d uc t i o n
2

to p rove t h a t 3

> n

fo r n a posi t i ve i n t e ge r g rea te r t h a n 2.

Sol u t i o n t o P r o b l e m 5:

n

> n

1

= 3 = 1

2

= 9 = 4

k

> k

## M u l t i p l y bo t h si des of t he above i neq u a l i t y by 3 3 * 3

k

> 3 * k

T he le f t si de is equa l to 3 k
2

k + 1

. Fo r k >, 2, we can w r i t e

> 2 k a nd k

> 1

## Jasvinder Singh, jasvinder.singh13@rediffmail.com

We now comb i ne t h e above i neq u a l i t i e s by add i n g t he lef t h a n d s ides and t h e r i g h t h a n d si des of t h e t w o i neq u a l i t i e s 2 k
2

> 2 k + 1

2

## to bot h sides of t he above i neq u a l i t y to ob ta i n t h e

> k

+ 2 k + 1

Fac to r t h e r i g h t si de we can w r i t e 3 * k
2

> ( k + 1)
k

If 3 * 3 3 * 3
k

> 3 * k
2

and 3 * k

> ( k + 1)

2 then

> ( k + 1)

Rew r i t e t h e le f t side as 3 3
k + 1

k + 1

> ( k + 1)

W h ic h p ro ves t h a P(k + 1) is t r u e

P r o b l e m 6: P rove t h a t n ! > 2
n

n

7

= 16

k

k

(k + 1)

## M u l t i p l y bo t h si des of t he above i neq u a l i t y by 2 2

k

to ob ta i n

(k + 1) > 2 * 2

T he above i neq u a l i t y ma y be w r i t t e n 2
k

(k + 1) > 2

k + 1

k + 1

(k + 1) a nd 2

(k + 1) > 2

k + 1

we